Prophylactic ephedrine to prevent postspinal hypotension following spinal anesthesia in elective cesarean section: A prospective cohort study in ethiopia - Tewoderos Shitemaw; Adugna Aregawi; Fissiha Fentie; Bedru Jemal (Wolters Kluwer Medknow Publications, 2019)
Introduction: Spinal anesthesia is commonly used for cesarean section (CS); however, hypotension is a common clinical problem after spinal anesthesia. Prophylaxis ephedrine can safely be administered by bolus intravenous (IV) route which is simple and cheap, because of its longer duration of action than other vasopressors. Methods: A sample size of 88 consecutive parturients scheduled for elective CS under spinal anesthesia was recruited for this study. Based on the responsible anesthetist's management plan, prophylactic group (Group 1) received IV prophylaxis ephedrine (10 mg) with fluid co-loading, while the nonprophylactic group (Group 2) received fluid co-loading only. The drug norepinephrine was used intraoperatively for the treatment of hypotension in both groups. The primary outcome was the incidence of hypotension. Secondary outcomes were blood pressure (BP), first hypotension incidence time, vasopressor for hypotension treatment, and pulse rate (PR). Results: Hypotension occurred in 22 [50.0% (95% confidence interval, CI, 35%-65%)] of patients in nonprophylactic group (Group 2) and 10 [22.7% (95% CI, 10%-36%)] of the patients in prophylactic group (Group 1) [X2 (1, N = 88) = 7.07,P= 0.008]. Mean values of systolic and diastolic BP were significantly different between groups from 5th min until the 20th min [P < 0.05]. The first hypotension incidence time was significantly different between groups with log rank test [P = 0.003]. Number of patient that required rescue vasopressor and total dose of rescue vasopressor were significantly different between the groups [19 (43.2%) vs. 6 (13.6%) and 7.5(5) vs. 15(15)], respectively. Differences in heart rate and Apgar score between groups were not statistically different. Conclusion: Prophylaxis IV bolus 10 mg ephedrine reduced the incidence of hypotension and greater arterial pressure stability was achieved following spinal anesthesia in parturient undergoing elective CS.